2013
DOI: 10.1038/mi.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal ureaplasma infection impairs development of the fetal ovine gut in an IL-1-dependent manner

Abstract: Ureaplasma infection of the amniotic cavity is associated with adverse postnatal intestinal outcomes. We tested whether interleukin-1 (IL-1) signaling underlies intestinal pathology following ureaplasma exposure in fetal sheep. Pregnant ewes received intra-amniotic injections of ureaplasma or culture media for controls at 3, 7, and 14 d before preterm delivery at 124 d gestation (term 150 d). Intra-amniotic injections of recombinant human interleukin IL-1 receptor antagonist (rhIL-1ra) or saline for controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Development of the fetal intestine was shown to be impaired in an IL-1-dependent manner in the context of chorioamnionitis. 17 Therefore, these results indicate that disturbed maturation of the intestinal epithelium during antenatal inflammation is the result of direct IL-1α effects to the GI mucosa. Alternatively, increased vacuolization and shortened villi at 6 days after IL-1α exposure to the fetal gut could also be interpreted as indicators of mucosal injury.…”
Section: Il-1α-driven Fetal Gut Inflammationmentioning
confidence: 83%
See 3 more Smart Citations
“…Development of the fetal intestine was shown to be impaired in an IL-1-dependent manner in the context of chorioamnionitis. 17 Therefore, these results indicate that disturbed maturation of the intestinal epithelium during antenatal inflammation is the result of direct IL-1α effects to the GI mucosa. Alternatively, increased vacuolization and shortened villi at 6 days after IL-1α exposure to the fetal gut could also be interpreted as indicators of mucosal injury.…”
Section: Il-1α-driven Fetal Gut Inflammationmentioning
confidence: 83%
“…17 In the present study, we evaluated the impact of IL-1α signaling on intestinal inflammation and injury when different epithelial organs were selectively exposed to IL-1α. Our findings indicate that the adverse outcomes of the fetal gut in the course of chorioamnionitis are the combined result of selective IL-1α-driven signaling of the lung, gut, and chorioamnion/skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ureaplasma has been detected in gastric aspirate samples from preterm human neonates, and experimental intrauterine Ureaplasma infection in pregnant sheep was found to impair development of the fetal ovine gut in an IL-1-dependent manner. 12,13 In addition, Okogbule-Wonodi et al, 14 have reported a 2-fold increased NEC prevalence in Ureaplasma-infected neonates born <33 weeks and a 3.3-fold increase in those born <28 weeks with Ureaplasma infection.…”
Section: Discussionmentioning
confidence: 98%